STUDY OF SEISMIC TOMOGRAPHY OF PAPANDAYAN VOLCANO : Abstract - NIM. 224 02 011, Kristianto
Abstract: Within June - July 1998 volcanic earthquakes of Papandayan Volcano increased. The average of volcanic earthquakes recorded was 4 events a day. During the period 7 digital earthquake recorder stations were installed around the volcano. Location of hypocenter of 60 volcanic earthquake events can be determined using Geiger method. Initial velocity 1-D model was determined by travel time curve (Telford., et al 1977). The minimum travel time from a source of earthquake to a receiver was calculated by ray tracing with a pseudo-bending method. The block element was choosen to be 2 x 2 x 2 km<sup3 based on distribution of earthquake receiver station and hypocenter. Input for seismic data inversion process is travel time difference between seismic wave in the earth (tobs) and seismic wave in the reference velocity model (tcal). While inverse problem uses approach of linear (Ax=dt) with LSQR method, with two damping type application; there are explicit and implicit damping. The explicit damping consists of minimum norm and gradient damping. Seismic tomography of Papandayan volcano gives a negative velocity anomaly structure 6-10 km depth from the reference below Walirang volcano or 4.6-8.6 km depth from Papandayan summit. The location is related to hot area. This result is supported by earthquake spectrum at 8-10 km in depth that indicates attenuation pattern when the seismic wave was passing negative velocity anomaly area.